PERAN DAN FUNGSI FILSAFAT PENDIDIKAN DALAM STRUKTUR KEILMUAN PONDOK PESANTREN: (Studi di Pondok Pesantren Mahasiswa Amanatul Ummah Ponorogo) - Ari Jalu Nur Khowin; Izzati, Leni Nurul; Ahmad Sulton (Jurnal Studi Pesantren, 2025)
This research in-depth analyzes the role and function of Islamic educational philosophy in shaping the scientific structure at the Amanatul Ummah Ponorogo Student Islamic Boarding School in the context of modernization challenges. By focusing on Islamic values, this research examines how Islamic boarding schools attempt to integrate traditional values ​​with the increasingly complex demands of the times, especially in facing globalization and developments in information technology. This research will identify the strategies implemented by Islamic boarding schools in maintaining the relevance of Islamic values, such as curriculum adaptation, use of technology in learning, and development of innovative learning models. Apart from that, this research will also discuss the challenges faced by Islamic boarding schools in dealing with value pluralism, radicalism and the current of secularism. Through in-depth analysis of the curriculum, learning methods, extracurricular activities, and in-depth interviews with kyai, teachers and students, this research aims to provide recommendations for Islamic boarding schools in developing educational models that are capable of producing graduates who not only master science, but also have good character. who is strong and adheres to Islamic values. This research will answer two main questions: (1) What is the role of educational philosophy in shaping the scientific structure at the Amanatul Ummah Ponorogo Islamic Boarding School? and (2) What is the function of educational philosophy in the educational context of the Islamic boarding school? It is hoped that the results of this research can make a significant contribution in understanding more deeply the role of educational philosophy in the context of modern Islamic boarding school education, as well as providing recommendations for developing Islamic boarding school education that is more relevant to the challenges of the times.